In-between discourses: Early intervention and diversity in the Norwegian kindergarten sector (Journal of Comparative Social Work, 2016)
During the last decades, early intervention has become a major concern across political parties in Norway. In line with the discourse of early intervention, kindergartens are perceived as important arenas for identifying children at risk and initiating intervention. Equally important in the kindergarten sector is the discourse of diversity, in which a tolerance for behaviours that deviate from the majority norm is assumed. Drawing on an institutional ethnography in Norwegian kindergartens, and in particular the concept of ruling relations, I compare these two discourses in this article and discuss how kindergarten staff have to negotiate between different, and sometimes conflicting, institutional discourses that can justify different interventions. As a consequence, and despite good intentions, kindergarten staff can end up treating children with different backgrounds unequally.